Enhancing the Nitrogen Use Efficiency in Bhindi With Nitrification Inhibitors - Bindu S Kurup (Department of Agronomy, College of Agriculture, 1994)
An experiment was conducted at the Instructional Farm, College of Agriculture, Vellayani inorder to find out the effect of nitrification inhibitors in enhancing the nitrogen use efficiency in bhindi. The treatments consisted of four levels of nitrogen viz., 50 kg ha-1, 100 kg ha-1, 200 kg ha-1 and 300 kg ha-1 and three nitrification inhibitors viz., urea, neem cake and mahua cake. Phosphorus and potassium were applied as per package of practices recommendation. The results revealed that nitrogen levels significantly influenced most of the growth and yield contributing characters, yield of bhindi, uptake of nutrients and available nutrient status of soil. Biometric observations like number of leaves, branches, root spread, DMP, LAI, RGR, NAR and CGR increased with increasing levels of nitrogen and the maximum was produced by the highest levels of nitrogen (300 kg ha-1). F1 produced the maximum height and F2 the longest tap root. Time of 50 per cent flowering and number of flowers per plant was maximum with the highest levels of nitrogen (F4). Whereas other yield contributing characters like number of fruits per plant, percentage of fruit set, length and girth of fruit, fruit yield per plant and total yield of bhindi was maximum with F2 (100 kg N ha-1 ). Quality aspects like crude protein and ascorbic acid content of fruits, uptake of nutrients by plant and fruit as also maximum with the highest levels of nitrogen (F4). However, the height of the first bearing node and chlorophyll content of leaves remain unchanged with increasing levels of nitrogen. The optimum level of nitrogen to get maximum fruit yield and net profit was worked out as 142 kg N ha-1 . Nitrification inhibitors caused significant variation in some of the characters like root spread, LAI RGR, NAR, CGR, number of flowers and fruits per plant, percentage of fruit set, length and girth of fruit, crude protein content and ascorbic acid content of fruit, uptake of nutrients by plant and fruit and available nutrient status of soil. In all these cases neem cake blended urea recorded the highest value followed by mahua cake blended urea. From the economic point of view, the maximum net profit of Rs. 11787.74 was obtained for neem cake blended urea and among nitrogen levels, 100 kg N ha-1 recorded the highest net profit of Rs. 16017.50. Thus neem cake blended urea at 100 kg N ha-1 can be suggested as the best economic dose of nitrogen for getting maximum yield and net profit.